ANALISIS TINGKAT PENGANGGURAN TERBUKA DAN UPAH MINIMUM DI PROVINSI JAWA BARAT - Lazuardi, Mohammad Afrizal; Santoso, Dwi Budi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
Unemployment is a macroeconomic problem that hinders regional development and gives rise to other social problems. West Jawa Province is the province with the highest open unemployment rate in Indonesia. Various factors contribute to this problem, so this research aims to explore the influence of the Minimum Wage and Economic Growth. This research uses secondary data 18 regencies and 9 cities in West Jawa Province and uses dynamic panel data regression analysis. The results of the study show that the results of the study show that when the minimum wage increases above the equilibrium, the demand for labor will decrease and the unemployment rate will increase. When economic growth increases, the demand for labor will increase which will ultimately reduce the unemployment rate.